PERAN KELUARGA DALAM MEMBINA AKHLAK REMAJA MUSLIM - Najwa Saefina, Khaila; Iqbal Amar Muzaki; Yadi Fahmi Arifudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In Islamic teachings, parents play a crucial role in their children's religious education. They are expected to be good role models for their children. The learning approach adopted by families has a significant impact on shaping the character and moral values ​​of young people. Families that demonstrate positive behavior and consistently instill religious teachings typically have well-behaved adolescents. Furthermore, good communication between family members creates opportunities for dialogue about the moral issues adolescents face in their daily lives. In the digital and globalized era, ethical issues are becoming increasingly complex, and the role of families is increasingly crucial in helping adolescents navigate them. Therefore, efforts to strengthen the family's role in shaping positive character in Muslim adolescents must be enhanced through the development of efficient family education programs and appropriate communication strategies.